Pengujian Kepuasan Wisatawan Muslim pada Paket Wisata Umroh - filda rahmiati (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
In this growing era, Umrah Travel business in Indonesia significantly growing rapidly. This study discussed an Examination of Muslim Travelers' Satisfaction on Umrah Tour Packages. Umrah services quality measured by accommodation, mobility, caretaking, food services, and problem solving. This research uses a quantitative research method and non-probability sampling with snowball sampling and distributed to 130 Muslim travellers. Tests used in this research were validity and reliability (as a pre-test), classical assumption tests and multiple regression test to test hypotheses. The result affirmed only hypothesis two (2) was rejected. It shows accommodation, caretaking, food services and problem solving have significant impacts on satisfaction, whereas mobility have not significant impacts on satisfaction. This study also shows that all variables in Umrah services quality (accommodation, mobility, caretaking, food services, and problem solving) have simultaneously significant impact on satisfaction of 36.6%